Enhancing Cancer Therapy: The Role of Melatonin and Herbal Medicine in Modulating Circadian Rhythms - Tavartkiladze, Alexandre (Journal of Medical Health Research and Psychiatry, 2024)
Melatonin, a hormone synthesized by the pineal gland during the dark phase of the circadian cycle, has been extensively studied for its ability to regulate circadian rhythms and its potential therapeutic applications in cancer treatment. The original article highlights melatonin's oncostatic properties, which include the induction of apoptosis in cancer cells, inhibition of tumor growth and proliferation, and enhancement of the efficacy of conventional chemotherapy and radiotherapy treatments. These properties underscore melatonin's potential as a valuable adjunct in cancer therapy. The synthesis and release of melatonin are closely linked to the body's circadian rhythms, serving as a physiological signal of darkness. This hormone influences various biological functions, including sleep regulation, immune response, and antioxidant defense mechanisms. Beyond these roles, melatonin's ability to regulate circadian rhythms suggests its potential in synchronizing the internal clock disrupted by cancer, thereby mitigating the adverse effects of circadian disruption on cancer prognosis.